2023
DOI: 10.1371/journal.pone.0283385
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic inequalities in burden of communicable and non-communicable diseases among older adults in India: Evidence from Longitudinal Ageing Study in India, 2017–18

Abstract: Developing countries like India grapple with significant challenges due to the double burden of communicable and non-communicable disease in older adults. Examining the distribution of the burden of different communicable and non-communicable diseases among older adults can present proper evidence to policymakers to deal with health inequality. The present study aimed to determine socioeconomic inequality in the burden of communicable and noncommunicable diseases among older adults in India. This study used Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…They are vulnerable to chronic diseases, and treatment-seeking is relatively low among them in poor households ( 22 , 23 ). Furthermore, the prevalence of communicable diseases among older adults will be high (24.9%) ( 24 ). During MDA, a majority of the older adult population refuse the drugs due to fear of adverse events, the need to consume a greater number of drugs, and the belief that they should not take drugs when they are not ill.…”
Section: The Older Adult Populationmentioning
confidence: 99%
“…They are vulnerable to chronic diseases, and treatment-seeking is relatively low among them in poor households ( 22 , 23 ). Furthermore, the prevalence of communicable diseases among older adults will be high (24.9%) ( 24 ). During MDA, a majority of the older adult population refuse the drugs due to fear of adverse events, the need to consume a greater number of drugs, and the belief that they should not take drugs when they are not ill.…”
Section: The Older Adult Populationmentioning
confidence: 99%
“…Bhise et al (2018) studied the NSSO 71st round and found the highest prevalence of NCD in southern states (107/1,000), and the lowest was recorded in the northeast (11/1,000) (Bhise et al, 2018). The increased life expectancy has been observed with increased prevalence of NCDs at older age, leading to mortality (Basu and King, 2013;Kundu and Chakraborty, 2023). An increase in the share of the working population will not automatically increase economic growth.…”
Section: Demographic Determinantmentioning
confidence: 99%